Notes on neural network learning and training - Wan Ishak, Wan Hussain (2004)
Neural Network (NN) could be define as an interconnected of simple processing element whose functionality is based on the biological neuron.Biological neuron (Figure 1) is a unique piece of equipment that carries information or a bit of knowledge and transfers to other neuron in a chain of networks.Artificial Neuron imitates these functions and their unique process of learning. Basically, biological neuron has three types of components called dendrites, soma and axon. Dendrites are the sensitive part of neuron that receive signal from other neuron.Soma calculates and sums the signals and transmitted to other cells through axon.